Acute Limb Ischemia and Outcomes With Vorapaxar in Patients With Peripheral Artery Disease: Results From the Trial to Assess the Effects of Vorapaxar in Preventing Heart Attack and Stroke in Patients With Atherosclerosis–Thrombolysis in Myocardial Infarction 50 (TRA2°P-TIMI 50). Issue 10 (8th March 2016) - Bonaca, Marc P.; Gutierrez, J. Antonio; Creager, Mark A.; Scirica, Benjamin M.; Olin, Jeffrey; Murphy, Sabina A.; Braunwald, Eugene; Morrow, David A.
Abstract : Background—: Patients with peripheral artery disease (PAD) are at heightened risk of acute limb ischemia (ALI), a morbid event that may result in limb loss. We investigated the causes, sequelae, and predictors of ALI in a contemporary population with symptomatic PAD and whether protease-activated receptor 1 antagonism with vorapaxar reduced ALI overall and by type. Methods and Results—: The Trial to Assess the Effects of Vorapaxar in Preventing Heart Attack and Stroke in Patients With Atherosclerosis–Thrombolysis in Myocardial Infarction 50 (TRA2°P-TIMI 50) was a randomized, double-blind, placebo-controlled trial of vorapaxar in stable patients, including 3787 with symptomatic PAD. ALI was a prespecified adjudicated end point using a formal definition. A total of 150 ALI events occurred in 108 patients during follow-up (placebo 3-year rate, 3.9%; 1.3% annualized). For patients with symptomatic PAD, previous peripheral revascularization, smoking, and the ankle-brachial index were predictive of ALI. The majority of ALI events occurred as a result of surgical graft thrombosis (56%), followed by native vessel in situ thrombosis (27%). Stent thrombosis and thromboembolism caused ALI in 13% and 5%, respectively. Amputation occurred in 17.6% presenting with ALI. Vorapaxar reduced first ALI events by 41% (hazard ratio, 0.58; 95% confidence interval, 0.39–0.86; P =0.006) and total ALI events by 41% (94 versus 56 events; risk ratio, 0.59; 95% confidence interval, 0.38–0.93; P =0.022). The efficacy of vorapaxar was consistent across types of ALI. Conclusions—: In selected patients with symptomatic PAD and without atrial fibrillation, ALI occurs at a rate of 1.3%/y, is most frequently caused by acute bypass graft thrombosis or in situ thrombosis of a diseased vessel, and often results in limb loss. Vorapaxar reduces ALI in patients with symptomatic PAD with consistency across type, including PAD resulting from surgical graft thrombosis and in-situ thrombosis. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00526474.